Design Of New Compounds Derived From Rosella Flavonoids As Diabetes Mellitus Enzyme Inhibitors Using Computer-Aided Drug Design Strategy - Oktavia Nanda lestari; Tiara Ajeng Litsyani; Septian Maulid Wicahyo (CV. AFDIFAL MAJU BERKAH, 2026)
Type 2 diabetes mellitus is increasing rapidly in Indonesia with a projected prevalence of 16.09% in 2045, requiring local plant-based α-amylase and α-glucosidase enzyme inhibitors such as the flavonoid kaempferol-3-O-rutinoside from roselle flowers (Hibiscus sabdariffa L.), which shows potential in silico inhibition but suboptimal ADMETox profile. This in silico computational experimental study aims to design kaempferol-3-O-rutinoside derivative compounds as effective inhibitors through computer-aided drug design, with a population of parent compounds, target enzymes, and acarbose as controls; purposive samples in the form of substituent modifications; PyRx-AutoDock Vina, SwissADME, Toxtree instruments; and molecular docking analysis techniques (ΔG, RMSD) and ADMETox prediction. The results showed a new compound with ΔGbind -5.0 kcal/mol (α-amylase, RMSD 1.538), -5.2 kcal/mol (α-glucosidase, RMSD 2.08), similarity of residues Asn A 570, Asp A 243, Val A 867, high GI absorption (molecular weight 340.41 g/mol, LogP 0.06), and low class I toxicity. In conclusion, the new compound has the potential as a safe oral antidiabetic drug candidate, in vitro/in vivo validation is recommended for further development